Exposure to agricultural pesticides by farmers of Chaimite administrative post - Sitoe, Marcio Daniel; Moiane, Gabriel Sidónio; Sitoe, Célia Cristina (Revista de Ciências Agroveterinárias, 2018)
The use of agricultural pesticides, has fundamental importance in reducing losses caused by pests and diseases, despite the risks to human health and the environment. The aim of this study was to analyze the agricultural pesticides exposure of farmers from Chaimite Administrative Post (AP), in Chibuto District, Gaza Province. A mixed questionnaire involving 40 Chaimite AP farmers were used. It was found that the most commonly used pesticides are Mancozeb, Cypermethrin and Methamidophos, which generally range from low toxic (Mancozeb) to very toxic (Methamidophos). The applicators are not sufficiently trained for safe and efficient work with pesticides, apart from not having a full KIT of Personal Protective Equipment (PPE), which makes them highly exposed and susceptible to poisoning, which can lead to loss of life. Therefore, it is necessary to make the access and use of PPE by family sector producers and training in pesticide application Technologies viable.